610 Peritoneal carcinomatosis index as a predictor of cytoreductive outcomes in patients with advanced ovarian cancer. (14th December 2020) - Yakovleva, Maria; Smirnova, Olga; Ulrikh, Elena; Bakaeva, Elvina; Petrova, Anna; Kozyreva, Ksenia; Shevkunov, Lev; Mikaya, Nikolay; Urmancheeva, Adel; Berlev, Igor
Abstract : Introduction/Background: In our study, we evaluated the peritoneal carcinomatosis index (PCI) and to study the influence of PCI on the cytoreductive surgery outcomes in patients with advanced ovarian cancer. Methodology: We analyzed the results of 133 patients with serous high-grade ovarian cancer FIGO IIIC-IVB stages. PCI was evaluated at 13 regions (score 0–3 for each region) via pelvic MRI, chest and abdominal CT and staging laparoscopy (S-LPS.) Results: Were performed 23% (31/133) of primary and 77% (102/133) of interval debulking surgery (DS), 68% (90/133) of them were optimal (no residual disease, ODS) and 32% (43/133) were suboptimal (residual tumor of > 1 cm, SDS). The frequency of ODS for PCI 0–15 score was 60–86%, for PCI 15–20 score - 9%, PCI> 20 score – 0%. Preoperative and intraoperative determination of the PCI was equal in 58%. In 19.8% PCI was overestimated during preoperative examination, while the use of laparoscopy evaluated PCI allowed to perform an ODS in these cases. In 21% PCI was underestimated and S-LPS helped to avoid SDS in 89% because of noting a diffuse bowel mesentery involvement. Conclusion: A combination of MRI/CT scans and staging laparoscopy in PCI evaluating is an effective treatment modality which can improve the cytoreductive outcomes in patients with advanced ovarian cancer. Disclosures: No conflict of interest exits in the submission of this study. We confirm that no funding source were used in this study.